Digitalization of Human Resource Management in MSMEs: An HRIS Systematic Review 2022–2025 - Mia Lestary; Bewi Meilita; Yuli Marhaini; Armalia Reny Wa (Penerbit Goodwood, 2026)
Purpose: This study aims to systematically review and synthesize recent scholarly work on the digitalization of Human Resource Management (HRM) in Micro, Small, and Medium Enterprises (MSMEs), with an emphasis on key themes, trends, technologies, challenges, and the implications of digital HRM for organizational performance and sustainability.Research Methodology: A Systematic Literature Review (SLR) was conducted in accordance with the PRISMA guidelines. Articles were retrieved from Scopus, Web of Science, and Google Scholar using keywords related to digital HRM, HR digitalization, HRIS, and MSMEs. The review covered studies published between 2022 and 2025. Based on predefined inclusion and exclusion criteria, 33 peer-reviewed articles were selected and analyzed through content analysis to identify the dominant themes and research gaps.Results: The review shows that digital HRM improves HR efficiency, supports data-driven decision-making, enhances employee capability development, and increases organizational agility in MSMEs. Nevertheless, its effectiveness is strongly influenced by managerial competence, digital readiness, and organizational culture, and key challenges include limited digital skills, resistance to change, and data security issues.Conclusions: Digital HRM is a strategic enabler of MSMEs’ competitiveness and long-term sustainability when aligned with managerial commitment and organizational capability.Limitations: This study was limited to English-language journal articles and secondary data within a defined period.Contribution: This study enriches the HRM and digital transformation literature by offering an integrated perspective and practical insights for managers and policymakers